(untitled) (Damascus University Journal for the economic and Political sciences, 2025)
This study aimed to determine the impact of human resources management practices (attraction and appointment, training and development, incentives and rewards, and performance evaluation) in achieving job loyalty from the point of view of employees in the Commercial Bank of Syria - General Administration. The researcher used the descriptive approach and adopted the questionnaire as a tool for the study, which was distributed to a sample of /194/ male and female employees in the bank. /189/questionnaires were retrieved, of which /178/ questionnaires were valid for statistical analysis. The conduct of appropriate specialized tests was analyzed using SPSS27, and the study reached results, the most important of which are: The level of human resources management practices in the bank under study reached the average level, and the sample employees enjoy an average level of job loyalty. It was also shown that there is a statistically significant effect of human resources management practices and all its dimensions represented by (recruitment and appointment - training and development - incentives and rewards - performance evaluation) in achieving job loyalty. The researcher presented a set of recommendations, the most important of which are: the necessity of working to modernize the rewards and incentives system, given its great impact on achieving Organizational loyalty, attracting them, and pushing them to perform work in an outstanding manner, and the necessity of activating the principle of putting the right person in the right place.